Structural and mechanical properties of La0.6Sr0.4M0.1Fe0.9O3-δ (M: Co, Ni and Cu) perovskites - Akbari Fakhrabadi, Ali; Meruane, V.; Jamshidijam, M.; Gracia Pinilla, Miguel Ángel; García, R.; Orellana, M. (Ceramurgica, 2016)
La0.6Sr0.4M0.1Fe0.9O3-δ (M: Co, Ni and Cu) perovskite nanostructures were synthesized using low frequency ultrasound assisted synthesis technique and effect of substitution of Fe by Co, Ni and Cu on crystal structure and mechanical properties in La0.6Sr0.4FeO3-δ perovskite were studied. The HRTEM and Rietveld refinement analyses revealed the uniform equi-axial shape of the obtained nanostructures with the existence of La0.6Sr0.4M0.1Fe0.9O3−δ with mixed rhombohedral and orthorhombic structures. Substitution of Cu decreases the melting point of La0.6Sr0.4FeO3-δ. The results of mechanical characterizations show that La0.6Sr0.4Co0.1Fe0.9O3−δ and La0.6Sr0.4Ni0.1Fe0.9O3−δ have ferroelastic behavior and comparable elastic moduli, however, subtitution of Ni shows higher hardness and lower fracture toughness than Co in Bsite doping